CHEMICAL COMPOSITION ANALYSIS OF MISCANTHUS PLANT LEAVES AND STEMS - Alamov, U; Shomurodov, D; Giyasova, N; Zokirova, Sh; Egamberdiev, E (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
A comparative analysis of the chemical composition of the leaves and whole plant stems of the cellulose-containing miscanthus plant shows that the values of indicators such as the mass fraction of protein, fat, ash and acid-insoluble lignin in the plant components are similar to those of the whole Miscanthus plant. high in wire; therefore, it is recommended to use whole Miscanthus plants, including leaves and stems, for further research aimed at developing the scientific and technological basis of processing and using Miscanthus biomass in fuel and energy, cellulose, microbiology and other fields.